The educational focus of physical training in the context of cadets' social and professional development - Afanasyeva I.A. ,; Kraeva E.S. ,; Dalskiy D.D. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to support the educational focus of physical training in the context of the social and professional development of cadets. Results and conclusions. The examination of scholarly research and educational practice in the realm of physical education within the context of higher education reveals that a variety of training programs and social engineering initiatives can serve as potent psychological and pedagogical instruments for fostering social communication abilities. These training programs are designed to enhance cadets' social communication and interaction skills within the framework of the physical education curriculum. They involve the demonstration and repetition of exercises to develop physical attributes. Additionally, they encompass a variety of search, project, and creative tasks aimed at discovering innovative approaches to increase physical activity. Furthermore, they encompass a range of situations that simulate interactions in professional settings, particularly in extreme circumstances where it is crucial to make joint decisions based on a specific level of physical fitness and personal and communicative abilities. These situations also include competitive game elements. Another method is social engineering, which involves creating future scenarios through the application of collaborative techniques.